(untitled) (Research, Society and Development, 2024)
Skin infections are conditions caused by microorganisms such as bacteria, fungi, viruses, or parasites that invade the skin and cause an inflammatory response. Among the diseases caused by bacteria are cellulitis, erysipelas, impetigo, acute lymphadenitis, skin abscess, scalded skin syndrome, furunculosis, Fournier’s gangrene, and necrotizing fasciitis, the first three of which are the most common. This ecological study aims to analyze the epidemiological profile of deaths from bacterial skin infections in Brazil from 2013 to 2022. Age groups were analyzed, distinguishing sex, race, and color. In this research, 49,211 cases of deaths due to skin infections were selected through the DATASUS database, in the TABNET tab in the Mortality option since 1996 by ICD-10. The results were represented and analyzed in a Microsoft Excel spreadsheet. It is concluded that there was a high number of cases of mortality from skin infections in elderly people aged 80 or over, with a higher incidence in white people and women. About the region, the southeast recorded the highest numbers of these cases.